Seropositivity of hepatitis B viral infection among liver disorder patients, voluntary blood donors and hospital personnel - Yadav, Vikas Chandra; Khan, Mohammad Zoyev; Agrawal, Sujan Narayan; Kiran, Vepada Ravi (International Journal of Research in Medical Sciences, 2016)
Background: HBV is highly infectious when compared with HIV even minute traces of infected blood as little as 0.0001 ml can transmit infection. Several of the routine therapeutic, diagnostic, prophylactic invasive procedures are capable of spreading HBV infection. Objectives of the study were to study the prevalence of hepatitis B surface antigen in voluntary blood donors, health care workers (medical and paramedical personnel) and patients with liver disorders Methods: Present study was hospital based cross sectional study carried out among 75 subjects during a period of one year. These 75 subjects consisted of 25 patients with liver disorder, 25 health care workers and 25 voluntary blood donors. All of these were selected randomly. After obtaining informed consent, detailed history and examination was carried out. The blood samples were collected and sent for detection of HBsAg by ELISA. Data was entered and analyzed using proportions. Results: Maximum subjects 40 (53.3%) belonged to the age group of 21-30 years overall as well as among the voluntary blood donors i.e. 60%. Among voluntary blood donors, 96% were males. 60% belonged to urban areas. Among rural subjects, maximum (53.3%) were having liver disorders. Only 28% were illiterate. Liver disorder was more common among illiterates i.e. it was 76.2%. Overall only 24% were having high risk behavior and all of them were heterosexuals. 76% were not having any high risk behavior. Liver disorder was more common (66.7%) among heterosexual high risk behavior subjects compared to only 22.8% with no high risk behavior. Seropositivity was found highest among patients with liver disorder (64%) followed by among health care workers (12%). No one was seropositive among voluntary blood donors. Overall the seropositivity was 25.4%. Conclusions: Patients with liver disorders especially chronic hepatitis were mostly seropositive. Among health care workers, being a doctor was an important risk factor for acquiring hepatitis B infection. Hence all health care workers should be immunized for hepatitis B.